Liquid Restriction for Patients With Chronic Kidney Disease to Prevent The Risk of Fluid Overload - Zahri Darni; Maryani Eka Sasmita (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
Chronic Kidney Disease is an end stage kidney disease which is a progressive and irreversible impairment of kidney function in which the body's ability to fail to maintain metabolism. This disease is a complication of hypertension, diabetes mellitus, pyelonephritis and acute renal failure. This study aims to describe the implementation of fluid restriction interventions to address the risk of fluid volume overload. The method used is descriptive with a case study approach with a sample of two patients. Methods of data collection by interview, observation, physical examination and documentation study. The data obtained were analyzed descriptively to describe changes in blood pressure, pulse frequency, respiratory rate, temperature, body weight and edema. The results of the case study showed no edema, blood pressure in subject I from 158/78 mmHg to 135/89 mmHg, subject II from 141/80 mmHg to 128/78 mmHg, pulse rate, respiratory rate, temperature within normal limits and body weight both subjects there is no increase. This case study recommends that nurses maintain fluid restriction settings to address the risk of fluid volume overload in Chronic Kidney Disease patients.